Pengaruh Pemberian Minyak Hati Ikan Hiu Botol (Centrophorus atromarginatus) Terhadap Kolesterol Total Darah Tikus Hiperkolesterolemia - Siti Fatimah; Muhammad Radifar; Tiara Madanti (Fakultas Farmasi Universitas Setia Budi, 2019)
Research has been conducted to determine the effect of bottle shark liver oil (Centrophorus atromarginatus) on total cholesterol levels of the blood of hypercholesterolemic rats fed high fat feed. This research was carried out experimentally using 25 male rats, aged 2-3 months with a weight of 150-200 g, which were divided into 5 treatment groups randomly, ie group K1 (normal control) were given standard feed, group K2 (positive control) given high fat feed for 7 days, while group P1, P2, and P3 were given bottle shark liver oil in a sonde with a dose of 54 mg / 200 mg / day, 108 mg / 200 mg / day, 216 mg / 200 g BW / day. Each treatment consisted of 5 rats which were examined 3 times the total cholesterol level by the CHOD-PAP method. Data obtained from examinations were analyzed using one-way ANOVA p <0.005 followed by post hoct test. The results of the P1, P2, and P3 groups were significantly different from K1 (p = 0,000). Groups P1, P2, and P3 were significantly different from K2 (p = 0,000). Bottle shark liver oil with a dose of 54mg / 200g BB / day, 108mg / 200g BB / day, 216mg / 200g BB / day each can reduce cholesterol levels by 23% or 43.67 mg / dl, 30% or 55, 72 mg / dl, and 38% or 70.94 mg /